Assistência estudantil na Universidade Federal do Ceará: avaliação do Programa de Residência Universitária - Oliveira, Saullo Pereira de (2024)
The Higher Education scenario in Brazil changed profoundly in the first decades of the 21st century, as a result of public policies to expand access implemented by the federal government. The increase in the number of vacancies made it possible for groups previously excluded from this level of education to enter the University. For those who enter, the problem of quality and permanence emerges, since access alone is not enough, it is necessary to guarantee the student's development in their academic trajectory. Decree No. 7,234, of July 19, 2010, which established the National Student Assistance Program (PNAES), was created in response to the problem of the lack of favorable conditions for low-income students to remain in higher education in the context of large expansion of federal public institutions and affirmative policies. The University Residency Program of the Federal University of Ceará (UFC), financed by the National Student Assistance Program (PNAES), has as its main objectives to enable students with socioeconomic difficulties to remain in face-to-face undergraduate courses at this educational institution, ensuring that they housing, quality food and seeking to facilitate access to the institution's health programs and units; and provide conditions that favor academic performance, among others. Considering the importance of the university residency program to democratize the conditions of access and permanence at the university, the following question arises that guides this research: how effective is the UFC University Residency Program? The general objective of this study was to evaluate the effectiveness of the University Residency Program at the Federal University of Ceará with a focus on the area of student housing, specifically the reality of university residences on the Fortaleza campuses. The relevance of this research lies in the fact that the results of this study will be fundamental for suggestions for improvements to the University Residency Program, within the scope of UFC student assistance. This is an exploratory, descriptive research with a qualitative-quantitative approach, based on bibliographical, field and documentary research. Data collection took place through the application of a questionnaire and direct observation. The results show the positive influence of the program on retention rates, however, it is necessary to improve the infrastructure of the residences in order to provide better conditions for the academic performance of residents, facilitate access to the institution's programs and health units, such as pedagogical support and psychological support, and improve the stimulation of the spirit of citizenship and community with the aim of reducing conflicts between residents. It is concluded that the University Residency Program partially fulfills its proposed objectives, contributing directly to the reduction of dropouts at UFC, to the satisfactory academic performance and student success of those benefiting from the public educational policy in question.